'Allowing One's Metaphors to Mix': Performances and Perspectives at the Peter Manson Symposium. Issue 1 (30th January 2019) - Sledmere, Maria; Bonetti, Denise
Abstract : Conference Report for The Peter Manson Symposium, organised by Ellen Dillon, Tom Betteridge, Colin Herd and Nicky Melville, which consisted of an informal evening of performances, and a day of panels and discussions in response to Manson's work.